Health-related quality of life does not predict mortality in idiopathic pulmonary fibrosis - Nishiyama, O.; Taniguchi, H.; Kondoh, et al., Y. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2012)
Background: Although health-related quality of life (HRQL) has recently been considered to be an important outcome in clinical trials of idiopathic pulmonary fibrosis (IPF), its relationship with survival is unknown. Objective: To determine the prognostic significance of HRQL scores in IPF assessed with the SGRQ. Design: Eighty-seven consecutive patients with IPF, who had undergone evaluations and completed the St. George’s Respiratory Questionnaire (SGRQ) at diagnosis were included in this study, as is the general practice. Cox proportional hazards analyses were performed to examine the relationship between HRQL scores and survival. Results: The mean observation period was 44.2±29.6 mo, in the course of which 54 patients (62.0%) died. Univariate analysis revealed that the activity scores in the SGRQ (HR: 1.016, 95% CI: 1.004-1.029, P=0.01) were significantly predictive of survival, although the symptoms, impacts, and total scores were not significantly related to mortality from all causes. However, multivariate analysis revealed that only the forced vital capacity percent predicted was a significant predictor of survival, and that the activity score in the SGRQ was not significantly related to mortality. Conclusions: There was no significant relationship between HRQL evaluated with the SGRQ and the subsequent mortality in IPF. The present negative result might suggest that HRQL is measuring an aspect other than one from physiological and functional impairment or disability.